Cyber-Security Threats and Challenges with Third Party Banking Partners - Dr. Umar Khalid Farooqui; Dr. Mohammad Husain (International Journal of Engineering and Management Research, 2021)
Cyber-security is a key topic of research studies and discussion in recent days. Due to our ignorance and lack of information, people are susceptible to risks and vulnerabilities in their daily banking operations. Attacks like malware, spoofing, phishing, DDOS, DOS, and many others are included in cyber-attacks, which primarily destroy the customer's information. Because of the ongoing rise in digitization and the continued use of outdated cyber-security measures, attacks intensified during the COVID-19 pandemic period. This paper discusses the dangers brought on by small-scale banking partners (often referred to as third-party vendors), whether those risks were intended or not. the manner in which the issue is made known to them beforehand so that they might avoid the dangerous circumstances.